Incidencia y tratamiento de parasitosis en niños y niñas que asisten a la Escuela Fiscal Mixta Héctor Toro Valarezo del sitio Vega Rivera de la Parroquia La Victoria de la ciudad de Santa Rosa en los meses de septiembre a noviembre del 2008 - Vásquez Tituana, Consuelo A. (2008)
Presently work was obtained the parasitosis incidence in children and girls that attend the School Fiscal Mixed Hector Bull Valarezo of the Vega Revera of the parish the Victoria of Santa Rosa´s city in the months of September to November of the 2008, for that which intended the following general objective: To determine the parasitosis incidence at school level and the treatment corresponding to the children and girls that attend the school to toast.